Penerapan Strategi Pembelajaran Outing Class dalam Meningkatkan Kecerdasan Naturalistik Anak Usia Dini - Khoirun N. Maulidiyah; Muhammad Mahfud; Umi Masturoh (JCE (Journal of Childhood Education), 2025)
Early childhood education requires learning strategies and methods that provide authentic learning experiences in order to achieve optimal child development. The development of naturalistic intelligence is one important aspect that needs to be stimulated from an early age, as it plays a crucial role in fostering children’s environmental awareness. This study aims to analyze the implementation of the outing class learning strategy in improving children’s naturalistic intelligence at RA Mambaul Ulum Driyorejo Gresik, as well as to identify its supporting and inhibiting factors. This research employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation. Data analysis was conducted using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings indicate that outing class activities, such as gardening, classifying plants, and recycling organic waste into fertilizer, are effective in fostering children’s environmental awareness and enhancing their naturalistic intelligence. Supporting factors include children’s enthusiasm, teacher competence, and the availability of a rich and diverse surrounding environment. Meanwhile, inhibiting factors consist of limited funding, weather conditions, and children’s increasing levels of activity. Therefore, the outing class strategy serves as a contextual and enjoyable learning approach that effectively promotes the development of naturalistic intelligence in early childhood.